Diversifikasi Produk Kesehatan Berbahan Dasar Minyak Atsiri Serai (Cymbopogon citratus (DC.) Stapf) - Favian Rafif Firdaus; Naima, Fathnin Ulya; Akbar, Achmad Naufal Maulana; Haq, Nimas Rizqi Firdausy; Lestari, Dewi; Setiawan, Catur Dian; Widyowati, Retno (Universitas Airlangga, 2024)
Lemongrass essential oil (Cymbopogon citratus (DC.) Stapf) had many benefits, including antibacterial, antifungal, anti-inflammatory properties, and effectiveness as a repellent against Aedes aegypti mosquitoes. These oils were processed into various household products, such as bar soap, carbolic floor cleaner, and aromatherapy candles. This research aimed to manufacture bar soap, carbolic floor cleaner, and aromatherapy candles on a laboratory scale that homemakers could replicate. Bar soap was made using VCO, palm oil, and olive oil, which were mixed with an NaOH solution. Aromatherapy candles were produced using solid paraffin that was melted and mixed with lemongrass essential oil, while carbolic floor cleaner was made using a combination of two phases: the oil phase, which used texapon, and the water phase, which used hexylene glycol. The results showed that the products had adequate physical characteristics and economic value. In addition to being beneficial for health, the products could also be marketed to increase family income. Keywords: Lemongrass Essential Oil, Health Products Formulation, Bar Soap, Aromatherapy Candles, Carbolic Floor Clearner